STORAGE METHODS INFLUENCE SOME PHYSICAL AND GRAVIMETRIC PROPERTIES OF JATROPHA (Jatropha curcas) SEEDS - Olajide Ayodele SADIKU; Matthew Ayoola OLUSEJE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Common storage methods and their effects on some engineering properties of Jatropha seeds were studied. Engineering properties of seeds are important in their handling, storage, processing and equipment design. Samples were collected from the Jatropha plantation in the Teaching and Research Farm of the University of Ibadan, Nigeria, populated with Jatropha assessions of age uniformity. Using standard methods, gravimetric properties (like true and bulk densities, porosity) and physical properties (like length, width, thickness, sphericity, surface area) of the seeds were determined for three months of storage at one month interval for crib, refrigerator and room storage methods. Data were analysed using GENSTAT Discovery (Edition 4). Means were separated using Least Significant Difference (LSD) at 5% probability level. The storage methods had no statistical significant effect on the physical properties while gravimetric properties were significantly affected. In the crib method, bulk density decreased (416 - 398 kg/cm3) and true density increased (709 - 820 kg/m3) while refrigerator showed increases in bulk (416 to- 432 kg/m3) and true (709 - 788 kg/m3) densities. For room method, true and bulk densities increased from 709 to 764 kg/m3 and 416 to 441 kg/m3 respectively. Porosity increased in the crib (41.3 – 51.4%), refrigerator (41.3 – 42.2%) and room (41.3 – 41.7%) methods. Therefore drying will be most efficient in crib method because of more pore spaces in the seed bulk. Baseline data of the physical and gravimetric properties of Jatropha curcas seeds required for machine and equipment design was generated.